PENERAPAN GOOD GOVERNANCE DALAM MENINGKATKAN KINERJA PEMERINTAH DESA DI DESA FATUARUIN KECAMATAN SASITAMEAN KABUPATEN MALAKA - Palmalius Putra Seran; Urbanus Ola; Veronika Ina Assan Boro (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2024)
This research aims to determine the Implementation of Good Governance in Improving Village Government Performance in Fatuaruin Village, Sasitamean District, Malaka Regency. The background to this research is that the application of Good Governance principles has a great influence on improving the performance of the Village government. The data analysis method used is a qualitative research method. The types of data used are primary data and secondary data, the data collection techniques used are observation, interviews and research location surveys, the data analysis technique used is qualitative analysis.The research results show that in Fatuaruin Village the application of Good Governance principles in the Village Government's performance in the Village is still not good enough, especially in terms of the principles of transparency and responsiveness.From the results of the research that has been carried out, the Fatuaruin Village Government should apply the principles of Good Governance in the Village, especially the principles of transparency and responsiveness so that the performance of the Village Government becomes better and must continue to apply the principles in accordance with those in Law number 06 of 2014 about the Village